The Distance between Us: Using Construal Level Theory to Understand Interpersonal Distance in a Digital Age - Norman, Elisabeth; Tjomsland, Hege E.; Huegel, David (Frontiers in Digital Humanities, 2016)
Several authors have shown how communication using digital devices influences the experience of psychological distance. For instance, the hyper-accessibility associated with mobile phones reduces the felt distance between people who are separated by geographical space (Cummings, Kraut, & Kiesler, 2001; Katz & Byrne, 2013; Sommer, 2002; Turkle, 2006). The current paper discusses how interpersonal distance, i.e., the perception of separation in space and time that people sense between themselves and others who are significant to them, is influenced by digital communication. It also explores the psychological mechanisms that can explain this influence. This work draws inspiration from construal level theory (Trope & Lieberman, 2010), as well as specific studies that have explored psychological distance in specific situations, e.g., in virtual work groups (Wilson, Crisp, & Mortensen, 2013) and real-time streaming video situations (Lim, Cha, Park, Lee, & Kim, 2012). Our contention is that construal level theory can be applied to understand the effect of digital communication on a broad range of human relationships.